Impact of pulmonary embolism on in-hospital mortality of patients with ischemic stroke - Keller, Karsten; Hobohm, Lukas; Münzel, Thomas; Lankeit, Mareike; Ostad, Mir Abolfazl (Journal of the neurological sciences, 2020)
Background - Pulmonary embolism (PE) is a frequent complication in immobile stroke patients and an important cause of death in stroke patients. We aimed to investigate predictors of PE and the impact of PE on survival of ischemic stroke patients. - Methods - Patients were selected by screening the German nationwide inpatient sample (2005-2017) for ischemic stroke (ICD-code I63) and stratified for occurrence of PE (ICD-code I26). Impact of PE on mortality and predictors for PE in ischemic stroke patients were analysed. - Results - Overall, 2,914,546 patients were hospitalized due to ischemic stroke (50.5% females; 69.3% aged ≥70years) in Germany 2005-2017. Among these, 0.4% had PE and 7.2% died during hospitalization. In-hospital mortality rate of ischemic stroke patients with PE was substantially higher compared to those patients without PE (28.4% vs. 7.1%, P<0.001). PE was strongly associated with in-hospital death (OR 5.786, 95%CI 5.515-6.070, P<0.001). Important predictors of PE were cancer (OR 3.165, 95%CI 2.969-3.374, P<0.001), coagulation abnormalities (OR 2.672, 95CI 2.481-2.878, P<0.001), heart failure (OR 1.553, 95%CI 1.472-1.639, P<0.001) and obesity (OR 1.559, 95%CI 1.453-1.672, P<0.001). Systemic thrombolysis was not beneficial regarding survival in unselected ischemic stroke patients. In contrast, systemic thrombolysis was beneficial in ischemic stroke patients without PE, who had to undergo cardio-pulmonary resuscitation (OR 0.866, 95%CI 0.782-0.960, P=0.006). - Conclusions - Patients with ischemic stroke revealed still a high in-hospital mortality of 7.2% in Germany. While only a minority of 0.4% of the ischemic stroke patients suffered from occurrence of PE, PE was accompanied by a substantial increase regarding in-hospital mortality. Systemic thrombolysis was beneficial regarding short-term survival in ischemic stroke patients without PE, who had to undergo cardio-pulmonary resuscitation.